Fibres: Future materials for advanced emerging applications - Fangueiro, Raúl (2012)
Fibrous materials are finding widespread applications in diversified areas, starting from clothing sector to medical fields, various structural and infrastructural applications of civil engineering, aerospace industries and even for energy harvesting and storage applications. In this paper, the results of various research activities conducted by the Fibrous Materials Research Group (FMRG), University of Minho to explore fibrous materials in several advanced and emerging applications have been presented and discussed.